Specifics of Bildungsroman Structure in Protocanon Phase of Socialist Realism - O. Yu. Osmukhina; E. P. Ovsyannikova (Научный диалог, 2024)
The article   examines   the   Soviet   novels of the mid-1920s — early 1930s, gravitating towards the genre tradition of the Bildungsroman (D. Furmanov’s “Chapaev”, A. Fadeev’s “Razgrom”, N. Ognev’s “Diary of Kostya Ryabtsev”, A. Gaidar’s “School”, A. Bondin’s “Matvey Korenistov”, B. Yasensky’s “A Man Changes Skin” and A. Avdeenko's “I Love”), which “prepared” the universal model of the socialist realist novel of the hero’s personality formation, largely determining its structure in the following decades. It is established that, first, the unifying feature of socialist realist novels about the formation of personality is an accentuated plot about the protagonist’s difficult childhood (the hero grows up in an incomplete family, the family does not participate in his upbringing), his escape from home and his discovery of a friend, who for the first time informs the hero of revolutionary sentiments; his functional role is a mediator on the border of two worlds — “old” and “new”. Secondly, one of the obligatory events in which the hero takes part is the rally (strike) as a place where the hero’s ideological allegiance is tested or where his views are formed. Third, the boundary event that separates the hero’s life in the narrative of the socialist realist novel is the October Revolution, participation in which allows the protagonist to find a “big family”. Finally, the narrative of the socialist realist Bildungsroman and re-education is an alternation of stable motifs: loneliness, recognizing mistakes, getting a second chance, and sacrificing oneself.